1996
DOI: 10.1038/hdy.1996.105
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of larval urea tolerance in Drosophila melanogaster

Abstract: The genetic control of larval tolerance to urea, a nitrogenous waste-product occurring naturally in crowded Drosophila cultures, was investigated in a set of five laboratory populations of D. melanogaster that had been successfully subjected to selection for increased larval urea tolerance. Larva to adult survivorship and development time at three different levels of urea were assayed on the five selected populations, their five matched controls and a set of 10 F1 hybrid populations derived from reciprocal cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…As the larvae sense an odor, they turn around and move towards the odor-causing substance, and crawling speed increases with concentration of the odorant (Hussaini et al . , 1985Joshi et al . Biotic residues are known to affect larval survival, development and female fecundity (Budnic & Brncic 1974, 1976Botella et al .…”
Section: Introductionmentioning
confidence: 99%
“…As the larvae sense an odor, they turn around and move towards the odor-causing substance, and crawling speed increases with concentration of the odorant (Hussaini et al . , 1985Joshi et al . Biotic residues are known to affect larval survival, development and female fecundity (Budnic & Brncic 1974, 1976Botella et al .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have shown that organisms respond to selection for increased resistance to environmental stresses, e.g. temperature (Bennett et al 1990;Huey et al 1991;Lenski and Bennett, 1993), starvation and urea (Gupta et al 1995;Joshi et al 1996). However, the genetic or physiological basis of evolved stress resistance is frequently unclear.…”
mentioning
confidence: 99%
“…These flies have been reared since 1980 on banana medium (normal food), under a 14-day generation cycle, at 25°C, with constant illumination. A urea-selected (MX) population was derived from each B population by providing larvae with banana medium containing urea (urea food) [10]. Adults were maintained in population cages with normal food, so that only the larvae were exposed to urea.…”
Section: Experimental Populations and Selection Protocolmentioning
confidence: 99%
“…The experimental generation consisted of four groups, each replicated fivefold: control populations reared on normal and 300 mM urea food, and urea-selected populations reared on normal and 300 mM urea food. Control populations reared on urea food develop through the larval stages, albeit more slowly than on normal food [10], but suffer nearly complete mortality during pupation [21]. All measurements were done on third-instar wandering larvae, the stage just prior to pupation.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation